Visual Outcomes after Cataract Surgery in Diabetic Patients - Abdul Rehman; Bukhari, Sadia; Ali, Irshad; Hussain, Shuja; Bashir, Ihsan; Paras (Indus Journal of Bioscience Research, 2025)
Background: Diabetes mellitus accelerates cataract formation and may negatively affect postoperative visual recovery. Although cataract surgery significantly improves vision, the presence of diabetes-related ocular changes can influence outcomes. Objective: To evaluate the visual outcomes after cataract surgery in diabetic patients and identify factors associated with postoperative visual recovery. Methods: This descriptive study was conducted at the Diabetic Eye Clinic of Al-Ibrahim Eye Hospital, Karachi, from June 2023 to June 2024. A total of 133 diabetic patients aged 40–65 years undergoing cataract surgery were enrolled through non-probability consecutive sampling. Baseline demographics, duration of diabetes, and ocular examination findings were recorded. Visual acuity was assessed preoperatively and at postoperative day 1, week 1, and month 1. Results: The mean age of patients was 54.7 ± 6.8 years, with 72 (54.1%) males and 61 (45.9%) females. Preoperatively, 98 patients (73.7%) presented with severe visual impairment (